Pengaruh Kualitas Program Electronic Medical Record (EMR) Terhadap Kepuasan Dokter Spesialis Dengan Kepatuhan Sebagai Variabel Mediasi Di Unit Rawat Jalan RS. Khusus Kanker Siloam MRCCC Tahun 2022 - Debora Claudia Lucas; Cicilia Windiyaningsih (Jurnal Manajemen dan Administrasi Rumah Sakit Indonesia (MARSI), 2022)
Satisfaction is the part of level feeling that is experienced by someone who knows the differences between hope and the result of work performance. The satisfaction in using a system will be very decisive wheter the person will be consistenly using and adopting it. The continuity of a programme depends on the user satisfaction itself. This research can be used to get the empirical evidence between the quality of Electronic Medical Record Programme, such as convenience, security, completeness, accuracy, availability, and structure of the specialist satisfaction and the obedience as moderation variable in outpatient department MRCCC Siloam Hospital 2022. This kind of research is a quantitative research with cross sectional research, with 40 specialist respondens in outpatient department actively. The datas are from questioner that is given to the specialist with informed consent. And the analysis used path analysis. Based on the research, we can conclude the significant result between quality of EMR with specialist satisfaction (C.R.>2,0 ; p<0,05) and the quality of EMR programme with specialist obedience in EMR progarmme filling(C.R.>2,0 ; p<0,05), however there is an effect between the obedience of specialist with specialist satisfaction (C.R.< 2,0; p>0,05) in outpatient department MRCCC Siloam Hospital. The research shows that the specialist doctor’s compliance variable does not effect a major role as a mediating variable between EMR uality and specialist satisfaction. Hospital need to increase the quality of EMR Programme especially in convenience and easiest access and also the completeness of supportive checking that is integrated with EMR Programme. Key words: Quality, Obedience, satisfaction